PENGENDALIAN MOTOR INDUKSI 3 FASA DENGAN BEBAN DINAMIS KONTROL PID FUZZY MENGGUNAKAN METODE FOC-TAK LANGSUNG (INDIRECT FIELD ORIENTED CONTROL) PADA LABVIEW - Hendra, R. Oktav Yama; Purwanto, Era; Oktavianto, Hary; Muntashir, Abdillah Aziz; Setiawan Suda, Kadek Reda (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This research includes the design of a PID speed control simulation combined with Fuzzy Logic Control as a control, and increasing the speed performance of an induction motor in LabView. The control method used is a vector control induction motor, namely Field Oriented Control. This method can set up an induction motor as easily as a separate amplifier DC motor. Fuzzy Logic Control with its advantages acts as a scheduler for the PID value with the advantage of increasing the dynamic performance of the induction motor against changes in load and speed changes. From several simulations carried out on LabView with 5nm and 9nm dynamic loads using the FOC method, the average risetime result is 80% fast. When testing the dynamic load control performance, the results of the PID-Fuzzy method are better than conventional PID, especially at high motor speeds and nominal loads. In dynamic load testing, PID-Fuzzy is also better than conventional PID. With a conventional PID controller when the load is 9nm with a set point of 1500 RPM, the risetime is 10.0 ms and the steady error is 1.8%. With the PID-Fuzzy method, a risetime of 6.6 ms is obtained and a steady error of 0.7.